Clinico epidemiological profile and trends of breast cancer over a decade: a study from UT of J&K, India - Gupta, Ashutosh; Gupta, Rajiv Kumar; Sharma, Rahul; Kumari, Rashmi; Kour, Sandeep; Katoch, Swarn Singh; Gupta, Rajeev; Sharma, Aproo (International Journal Of Community Medicine And Public Health, 2026)
Background: Breast cancer remains one of the leading causes of malignancy related deaths in women. Understanding the burden of disease and its epidemiology including risk factors are fundamental to public health preventive measures. The study explored the clinic-epidemiological profile and trends of breast cancer in Jammu province of UT of J&K, India. Methods: Hospital Based Cancer Registry (HBCR) has been in operation since 2014 in Government Medical College Jammu. The data from 2014-2024 was collected as per socio demographic variables, district wise residence and detailed information about clinical profile of the patients. The data was represented as frequency and proportions while trends were reflected using line diagram. Results: Almost one-third of the patients (30.3%) were in the 45-54 years age group. Similar proportion of the patients was found to be in premenopausal age group. 91% of the patients were married and 63.11% of the total were illiterate. District wise distribution of the patients revealed that almost half (51.60%) of the total belonged to Jammu district. Majority (94.8%) has infiltrating ductal carcinoma on histopathology. At the time of presentation 41.36% were in Stage-II of the disease. Conclusion: The trends of breast cancer reveal that disease has a steady path with peaks in 2018 and 2019. One third of patients in pre-menopausal age group is a cause of concern. Authors recommend continuous health education regarding warning signals of breast cancer and it’s early screening so that these patients can be diagnosed and treated at an earlier stage.